NGC 3147: a prototypical low-luminosity active galactic nucleus with double-peaked optical and ultraviolet lines. Issue 4 (16th August 2022) - Bianchi, Stefano; Chiaberge, Marco; Laor, Ari; Antonucci, Robert; Bagul, Atharva; Capetti, Alessandro
ABSTRACT: A previous narrow-slit (0.1 arcsec) Hubble Space Telescope observation unveiled a broad relativistic Hα profile in NGC 3147, a low-luminosity ( L bol ∼ 10 42 erg s −1 ), low-Eddington ratio ( L bol / L Edd ∼ 10 −4 ) active galactic nucleus (AGN), formerly believed to be a candidate true type 2 AGN intrinsically lacking the broad-line region. The new observations presented here confirm the double-peaked profile of the Hα line, which further shows variability both in flux and in the inner radius of the emitting disc with respect to the previous epoch. Similar disc line profiles are also found in prominent ultraviolet (UV) lines, in particular Lyα and C iv . The new data also allow us to build a simultaneous subarcsec optical-to-X-ray spectral energy distribution of NGC 3147, which is characterized by the absence of a thermal UV bump, and an emission peak in the X-rays. The resulting very flat αox = −0.82 is typical of low-luminosity AGNs, and is in good agreement with the extrapolation to low luminosities of the well-known trend with luminosity observed in a standard AGN. Indeed, we are possibly observing the accretion disc emission in NGC 3147 in the optical, close to the expected peak. On the other hand, the steep −2 UV power law may be Comptonization of that cold disc by a warm corona, what is instead generally observed as a 'soft excess' in a more luminous AGN.